A\NATURAL MONTMO RILLONITE-ORGANIC FROM ALLEPPEY, KERALA STATE--INDIA COMPLEX - JOHAN MOUM, CHATTY N. RAO and T. S. R. AYYAR (Clays and Clay Minerals, 1973, Vol. 21, pp. 89-95., 1973)
A\black organic-rich alluvial clay from Alleppey, Kerala State, India, gave a well defined17~, reflection in the natural untreated state. Ethylene glycol and heat treatments showed it to be essentially a smectite. Treatments with H~O2 and 0.1 N NaOH contracted the spacing to about 14A, indicating that sorbed organic matter was responsible for the original enhanced spacing. In the natural state, the clay was chiefly divalent with respect to the ions on its exchange sites and was at a pH of 6-2. Subsequent attempts to resorb the organic matter (which had been extracted from the clay by repeated NaOH treatments, converted to the H-form, concentrated and reeze-dried) into the interlamellar space of H202-treated clay proved successful only after the pH was brought down to 3.2 and the clay converted to an essentially monovalent state through repeated 1 N NaCI treatments.